PALMARI GPS INTEGRATI NELLA GESTIONE DEL VERDE DI MILANO Un sistema di controllo della qualità a supporto della pianificazione - Franco Guzzetti; Anna Privitera; Manuela Re; Paolo Viskanic (GEOmedia, 2013)
Green public spaces within cities are precious resources that have to be safeguarded and enhanced as public assets with an important environmental and social role. The municipality of Milano has developed a GIS-based management system, which allows managing, monitoring and documenting all maintenance activities, while ensuring an agreed level of quality. The activities are carried out by external companies, in the framework of a Global Service. In order to monitor the quality of green areas, municipal controllers and operators in the field monitor quality standards and report non compliance cases using handheld GPS devices. The geo-referenced reports are then matched with the elements in the GIS and forwarded to the gardeners in charge of the area. This article analyses the result of one year of use of GPS devices in the field, the problems encountered, and the improvements made in the overall green area management in the City of Milano.